Butyrate interacts with the effects of 2’FL and 3FL to modulate in vitro ovalbumin-induced immune activation, and 2’FL lowers mucosal mast cell activation in a preclinical model for hen’s egg allergy - Zuurveld, M.; Diks, M. A. P.; Kiliaan, P. C. J.; Garssen, J.; Folkerts, G.; van’t Land, B.; Willemsen, L. E. M. (Frontiers in Nutrition, 2023)
Early life provides a window of opportunity to prevent allergic diseases. With a prevalence of 0,5-2% in infants, hen’s eggs allergy is one of the most common food allergies. The immunomodulatory effects of human milk oligosaccharides (HMOS), 2’-fucosyllactose (2’FL) and 3-fucosyllactose (3FL), were studied in an in vitro mucosal immune model and an in vivo murine model for hen’s egg (ovalbumin) allergy. Intestinal epithelial cell (IEC)/dendritic cell (DC) and DC/T cell cocultures were used to expose IEC to ovalbumin (OVA) in an in vitro mucosal immune model. The effects of epithelial pre-incubation with 0,1% 2’FL or 3FL and/or 0,5mM butyrate were studied. 3-4 Weeks-old female C3H/HeOuJ mice were fed AIN93G diets containing 0,1%-0,5% 2’FL or 3FL two weeks prior to and during OVA sensitization and challenge. Allergic symptoms, systemic and local immune parameters were assessed. xposing IEC to butyrate in vitro left the IEC/DC/T cell crosstalk unaffected, while 2’FL and 3FL showed differential immunomodulatory effects. In 3FL exposed IEC-DC-T cells, the IFNγ and IL10 secretion was enhanced. This was observed upon pre-incubation of IEC with 2’FL and butyrate as well, but not 2’FL alone. The presence of butyrate did not affect OVA activation, but when combined with 3FL an increase in IL6 release from DCs was observed (p<0.001). OVA allergic mice receiving 0,5% 3FL diet had a lower %Th2 cells in MLNs, but the humoral response was unaltered as compared to control mice. OVA-allergic mice receiving 0,1 or 0,5% 2’FL diets had lower serum levels of OVA-IgG2a (p<0.05) or the mast cell marker mMCP1, in association with increased cecal short chain fatty acids (SCFAs) concentration (p<0.05). In vitro butyrate exposure promotes the development of a downstream type 1 and regulatory response observed after 2’FL exposure. 2’FL and 3FL differentially modulate ovalbumin induced mucosal inflammation predominantly independent of butyrate. Mice receiving dietary 3FL during ovalbumin sensitization and challenge had lowered Th2 activation, while the frequency of Treg cells was enhanced. By contrast, 2’FL improved the humoral immune response and suppressed mast cell activation in association with increased SCFAs production in the murine model for hen’s egg allergy.